COMPARISON BETWEEN HYDRO- AND OSMO-PRIMING TO DETERMINE PERIOD NEEDED FOR PRIMING INDICATOR AND ITS EFFECT ON GERMINATION PERCENTAGE OF AEROBIC RICE CULTIVARS (Oryza sativa L.) - Elkheir Hassaballah Abdallah; Yunus Musa; Muslimin Mustafa; Rinaldi Sjahril; Muhammad Riadi (AGRIVITA, Journal of Agricultural Science, 2016)
This study compared hydro- and osmo-priming to determine period needed for seed priming indicator to emerge and its effect against water stress on germination percentage of some aerobic rice cultivars (Oryza sativa L.). Experiments were arranged in completely randomized design using three aerobic rice cultivars and PEG with four replications. Rice varieties (Inpago-8, IR64 and Situ Bagendit) were combined with four different PEG concentrations. Drought stress was simulated by different PEG solutions and with distilled water as control. Results indicated differentiations between hydro and on priming indicator time, while varietal difference was not significant. Fastest recorded time was obtained between 30-36 hours under hydro priming, PEG 100 g L-1 (63-69 hours) and 83-93 hours in PEG 200 g L-1 solution. Thus showing increased solution concentration led to prolonged priming indicator time. The highest germination percentage was obtained in Situ Bagendit treated with PEG 200 mg L-1 (90.25%) and the lowest obtained in Inpago-8 (75.75%) under control. It is better to use osmo-priming (PEG 200 g L-1) for teaching aerobic rice seed against drought stress. More research is needed to confirm benefits of seed treatment with PEG to cultivated crops under water stress, drought and salinity conditions.